Complex Treatment of Anastomositis: The Role of Lymphatic Stimulation and Radiation Therapy - Lukas J. Müller, Andrew I. Chambers (Academic Journal of Clinicians, 2024)
Anastomositis is a significant complication that can occur following surgical procedures involving anastomosis, leading to inflammation and impaired healing at the site of the anastomotic junction. This structured abstract provides an overview of the role of lymphatic stimulation and radiation therapy in the complex treatment of anastomositis. Lymphatic stimulation techniques, such as manual lymphatic drainage and pneumatic compression, have shown promise in managing anastomositis by improving lymphatic flow and reducing edema. These techniques promote tissue drainage, enhance immune response, and facilitate the removal of inflammatory mediators, thereby aiding in the resolution of anastomotic inflammation. Radiation therapy has also emerged as a potential modality in the treatment of anastomositis. Low-dose radiation therapy can modulate the inflammatory response, promote tissue regeneration, and reduce fibrosis, leading to improved healing outcomes. However, the optimal dosage, timing, and fractionation of radiation therapy in the context of anastomositis remain areas of ongoing research